PERANCANGAN KONTROL SISTEM INTEGRATOR MULTI AGEN DENGAN FORMASI SEGITIGA - tjahjana, remedetus heru (MATEMATIKA, 2010)
In this paper, a model of swarm movement in triangular formation is considered. The flocking of geese happening in nature motivates this model. The model is described by several integrator systems. The movement of the swarm formation is required to preserve a triangle formation from one particular position to the other position. The triangular formation above is translated to a functional cost that must be minimized. This functional cost consists of an error function, repellant term and energy put to control each agent. The theorem of swarm movement in a triangular formation and some simulation results are presented in the end of the paper.